Essays on regulatory instuments : leniency and anti-dumping - Marvão, Catarina (Trinity College (Dublin, Ireland). Department of Economics, 2014)
In this thesis I explore two specific regulatory instruments, from a theoretical standpoint and from an empirical perspective. In particular, I address the regulation of leniency in relation to EU and US cartels and the regulation of the alleged dumping of products exported into the EU.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin